2016
DOI: 10.1080/14719037.2016.1148193
|View full text |Cite
|
Sign up to set email alerts
|

The politics of cutback management in thirteen European countries: statistical evidence on causes and effects

Abstract: The politics of fiscal consolidation in thirteen European countries are statistically analysed. Based on the political economy literature, political factors are identified that explain for the consolidation. Variables are selected representing strength of government and political orientation, and fiscal consolidation is distinguished into spending cuts and cuts in administration. The statistical analysis of political explanations for cutbacks hardly yields significant results and nor does the analysis of fisca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 31 publications
1
11
0
2
Order By: Relevance
“…First, a quantitative analysis of the whole sample shows that the cyclically adjusted measure of fiscal discipline does not correlate with standard political economy variables concerning the composition of government. This is consistent with the previous literature, which reports that the usual variables of political economy and fiscal institutionalism do not perform well in explaining fiscal discipline (Kickert and Randma-Liiv, 2017). Second, we report a qualitative discussion of two extreme country cases, the Netherlands and Spain.…”
Section: Introductionsupporting
confidence: 91%
See 1 more Smart Citation
“…First, a quantitative analysis of the whole sample shows that the cyclically adjusted measure of fiscal discipline does not correlate with standard political economy variables concerning the composition of government. This is consistent with the previous literature, which reports that the usual variables of political economy and fiscal institutionalism do not perform well in explaining fiscal discipline (Kickert and Randma-Liiv, 2017). Second, we report a qualitative discussion of two extreme country cases, the Netherlands and Spain.…”
Section: Introductionsupporting
confidence: 91%
“…However, this has been openly questioned theoretically (Cusack, 1999), and it is not backed up empirically (Imbeau et al, 2001;Eslava, 2011;Armingeon, 2012;H€ ubscher, 2016). Indeed, an analysis of the fiscal consolidation episodes of 13 EU countries in the aftermath of the global recession fails to find support for the claim that the strength of governments or their political orientation has had a significant effect on the size and composition of fiscal consolidation (Kickert and Randma-Liiv, 2017).…”
Section: Literature Review: the Determinants Of Fiscal Disciplinementioning
confidence: 99%
“…The analysis focuses purely on the Danish local government context, which covers a standard range of services but there is always the chance that research findings do not readily transfer to other settings. Finally, we analyse a limited time period and extended longitudinal research might capture more substantial shifts in employment, along with the longer term effects of the global financial crisis on employment growth (Kickert and Randma-Liiv 2016).…”
Section: From Table 1 It Is Clear Thatmentioning
confidence: 99%
“…Estonia was one of the first European countries to implement immediate and radical cutbacks as early as 2008. It was also the only country in Europe where the government in power won the general elections shortly after the cutbacks (Kickert and Randma-Liiv 2017). This paper sheds light on how these seemingly contradictory consequences of the fiscal crisis came about.…”
Section: Conclusion and Discussionmentioning
confidence: 86%
“…Interestingly enough, the government responsible for the austerity measures was re-elected with a strengthened mandate in a general election in March 2011. A comparative study of seventeen European governments (Kickert and Randma-Liiv 2017) showed that general elections in all but Estonia's case resulted in a defeat of any incumbent government that had taken steps towards fiscal consolidation. In the 2011 general elections, the electorate saw the Estonian government's perceived success in joining the Eurozone as sufficient compensation for the radical cutbacks.…”
Section: Fiscal Consolidation In Estoniamentioning
confidence: 99%